Analisis Potensi, Efektivitas Pemungutan, dan Kontribusi Pajak Hotel pada Pendapatan Asli Daerah - Cahya Pramadya Utami, Putu; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2020)
The purpose of this study was to determine the magnitude of the potential, effectiveness of collection, and hotel tax contributions in the District of South Kuta as a source of PAD in Badung Regency. This research was conducted at 54 star hotels, 50 jasmine hotels, and 88 tourist lodges in South Kuta District with the method of determining the sample of simple random sampling. Data collection was carried out through non-participant observation and surveys. The analysis technique used is quantitative descriptive. Based on the results of the study found the magnitude of the hotel tax potential in the District of South Kuta, amounting to 1,857,185,535,800 rupiah. The effectiveness of tax collection is 66 percent and classified as less effective. The contribution of hotel taxes in Kuta Selatan District is 10 percent of Badung Regency's PAD revenue. Keywords: Potency; Effectiveness; Contribution; PAD.